Legitimidade passiva na ação civil pública ambiental de conhecimento condenatória - Lima, Cintia Roberta Gomes de (2004)
The present essay concerns the study of the passive legitimacy in environmental public civil lawsuit of condemnatory knowledge. While the active legitimacy is determined by the established country's legislation, the passive legitimacy has no expressed legal prevision and there are a few scientific productions concerning the subject. So, this essay is exactly aimed to identity who, in the public civil lawsuit, is the defendant in order to obtain compensation for losses or damages caused to environment. Starting from the premise of procedure law instrumentality and its interaction with the substantial law, the topic, inherent to the procedure law, is developed based on the institutes of the environmental material law, because it is from the material law relation that the legitimacy is drawn for the juridical procedure relation. All the study is based on discerning doctrinaire research, being cited judicial verdicts which offer support to the developed argumentations. It concludes the legitimated liabilities for the environmental public civil lawsuit of condemnatory knowledge is the one, that by the rules of material law, is indicated as the polluter, because he is the one that directly or indirectly caused the environmental damage and so, has the obligation to repair it. It is also obvious that in the reason of the juridic nature of environmental property and the rules of responsibilities, objective and solidary, that are in force in the environmental law, the intervention of third party in the passive pole of the processual relation and passive litisconsortium institution, should be avoided, unless the necessary, it is always at the plaintiff discretion